Empirical Study of Far-Field Radio Frequency Wireless Power Transfer Testbed for Underground Mines Based on 1.8 GHz - Anabi Hilary Kelechi; Frimpong Samuel (IEEE Access)
A novel 1.8 GHz far-field wireless power transfer (WPT) testbed was designed to achieve long-distance energy harvesting in underground mine (UM). Prior experimental studies confirm that underground mines experience 50 dB radio frequency (RF) signal attenuation compared to a typical wireless environment. Due to this severe signal attenuation, the currently proposed radio frequency energy harvesting (RF-EH) testbed cannot be deployed in underground mines. In this study, we proposed, designed and performed an empirical study with a military-grade class A radio frequency wireless power transfer (RF-WPT) testbed. The various digital modulation schemes experimented with included: BPSK, DBPSK, QPSK, OQPSK, Pi4DQPSK, 8PSK, D8PSK,16PSK, QAM16, QAM 64, QAM 256, QAM 1024, 2ASK, 2FSK, 4FSK, 8FSK, 16FSK, and OFDM. With the proposed testbed, we successfully performed long-distance WPT in an underground mine at 20 meters by harvesting 4.2 volts DC with a Powercast P21XXCSR-EVB RF-EH receiver. We are specifically interested in understanding the optimal digital modulation scheme from the perspective of WPT efficiency in real-world deployment scenarios. Based on the outcome of this study, the optimal modulation scheme/s for WPT and wireless information transfer (WIT) in a simultaneous wireless information and power transfer (SWIPT) technology is established and amongst the various digital modulation schemes experimented with, 2ASK, 2FSK, 4FSK, 8FSK, 16 FSK, and Pi4DQPSK exhibited high performance based on the maximum power transfer distance. Therefore, we recommend them as good candidates for WPT in digital wireless communications. The research also compared the impact of using Yagi and omnidirectional antennas. It was observed that the omnidirectional antenna suffers a 5-meter performance loss compared to the Yagi antenna. Additionally, we mimicked a multipath wireless channel by introducing an N directional 15 dB coupler at the transmitter side, it was observed that there is an absence of multipath effect in UM, and hence, antenna diversity and MIMO technology will perform poorly in UM.